The Stumbling and Building of Noodle Bowl Effect of Convergence of Trans-Pacific Partnership (TPP) and Regional Comprehensive Economic Partnership (RCEP) - Dayang Affizzah, Awang Marikan; Ting Mei, Sing; Nurul Aida, Abdullah (HRMARS, 2021)
The study focus on convergence in 12 countries TPP (Trans-Pacific Partnership) and 16 countries RCEP (Regional Comprehensive Economic Partnership) member countries, particularly in respect to total trade for the period 2000-2017. This study uses the non-linear approach model, transition Path, and log t-test by Philip and Sul. The Trans-Pacific Partnership’s overall convergence among member countries shows it is diverging, and clustered themselves into four convergence clubs. As for Regional Comprehensive Economic Partnership’s overall convergence reflects it is converging though could be interpreted as a weak convergence, and clustered themselves into four convergence clubs. The study concludes that it is keen towards RCEP, as it shows more similarities and unity among participating member as to compare with TPP.